Komunikasi Persuasi Eksistensi Remaja Pada Media Sosial - Sutrisno, Andika Agung; Herwanto, Andhika Putra (Efektor, 2019)
Social media is a link to expand relationships and get a lot of information in the distance, space and time of receiving and sending messages quickly. The presence of various kinds of communication and electronic devices available in the community whose function is no longer out of necessity but as part of a lifestyle and prioritizing existence, the easier it is to get various data access information without being filtered or controlled. Because users of this technological development in Indonesia are even partly dominated by young children and adolescents, even elementary school age children. As we know, children and adolescents do not have enough emotional maturity and moral knowledge, so they are easily influenced by the outside environment. Awareness programs are needed to wisely use social media. Campaign activities that focus on the attention of the public or the wider community towards ignorance, addiction, are not wise in utilizing technology that leaves the humanism side. Campaign activities that can be carried out can use unlimited media that is expected to be effective from the message to be conveyed can be delivered on target.